A society in transition: Developmental and seasonal influences on the nutrition of Maasai women and children - Nestel, P. (United Nations, 1986)
Presents findings of research conducted to identify how the Maasai manage their livestock to achieve their subsistence food requirements and production goals; to determine the casual relations within the production system, and to elucidate the constraints on livestock production and evaluate potential interventions designed to increased productivity.